The Changing of Important Factors in The Landscape Planning Occur Due to Global Climate Change in Temperature, Rain and Climate Types: A Case Study of Mersin City - Mehmet Cetin (Turkish Journal of Agriculture: Food Science and Technology)
Global climate change is seen as a process that will directly or indirectly affect living things and ecosystems all over the world. In this process, determining the changes in climate parameters and climate types in advance is of great importance in terms of the measures that can be taken and the preparation for the process. In this study, it is aimed to determine the changes that may be caused by global climate change in some climate parameters and climate types in Mersin, which is one of the important cities of our country. Within the scope of the study, the current status of temperature, precipitation and climate types (according to De Martone and Emberger climate classification) and RCP 4.5 and RCP 8.5. It is aimed to compare the possible situations in 2050 and 2070 in the light of scenarios. The results of the study show that temperature, precipitation and climate types will change significantly throughout Mersin province. Today, the temperature varying between -0.4°C and 19°C will change between 4.9°C and 24°C throughout the province in 2070 according to the RCP 8.5 scenario, that is, there will be an increase of around 5°C in the temperature change interval, the precipitation regime will change, Climate types are predicted to shift towards arid climates. This situation shows that climate factors, one of the most important planning criteria, will change significantly in landscape planning studies. Since landscape planning studies continue their effects for many years, it is recommended to take this into consideration in order to make a healthy planning. The results of this study should be used in the planning studies for Mersin province.